2010
DOI: 10.1182/blood-2010-01-265751
|View full text |Cite
|
Sign up to set email alerts
|

Reimplantation of cryopreserved ovarian tissue from patients with acute lymphoblastic leukemia is potentially unsafe

Abstract: Ovarian tissue cryopreservation is currently proposed to young cancer patients to preserve their fertility before radiochemotherapy. The potential risk is that the tissue might harbor malignant cells that could induce disease recurrence. We therefore decided to evaluate the presence of leukemic cells in cryopreserved ovarian tissue from 18 leukemic patients: 6 with chronic myeloid leukemia (CML) and 12 with acute lymphoblastic leukemia (ALL). In each case, histology, quantitative reverse-transcribed polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
277
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 382 publications
(315 citation statements)
references
References 38 publications
13
277
1
8
Order By: Relevance
“…Breast tumor tissue (infiltrating ductal carcinoma) was grafted to an additional SCID mouse as a positive control for long-term xenografting. The grafting protocol used in this study was the same as previously described [11]. Briefly, a small median slit was made in the abdomen and peritoneum of the animals, and human ovarian tissue strips were fixed to the inner side of the peritoneum with one or two stitches of 6-0 Prolene (Fig.…”
Section: Transplantation To Scid Micementioning
confidence: 99%
See 2 more Smart Citations
“…Breast tumor tissue (infiltrating ductal carcinoma) was grafted to an additional SCID mouse as a positive control for long-term xenografting. The grafting protocol used in this study was the same as previously described [11]. Briefly, a small median slit was made in the abdomen and peritoneum of the animals, and human ovarian tissue strips were fixed to the inner side of the peritoneum with one or two stitches of 6-0 Prolene (Fig.…”
Section: Transplantation To Scid Micementioning
confidence: 99%
“…Morphological and immunohistochemical studies may not be sensitive or specific enough to identify malignant microinvasion of ovarian tissue, and more sensitive methods such as long-term xenografting and qPCR analyses are mandatory. These techniques were used to detect leukemic cells in cryopreserved ovarian tissue [11], with qPCR proving positive in 9 out of 16 ovarian tissue samples from leukemia patients. After xenografting, 4 out of 12 mice presented with malignant invasion.…”
Section: Breast Metastasis In Ovarian Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified malignant cells in cryopreserved ovarian tissue of leukemia patients by sensitive PCR [17][18][19] and flow cytometry [20] analysis. In one study, the tumor-inducing potential of leukemic cells present in ovarian tissue was demonstrated in a xenografting model [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified malignant cells in cryopreserved ovarian tissue of leukemia patients by sensitive PCR [17][18][19] and flow cytometry [20] analysis. In one study, the tumor-inducing potential of leukemic cells present in ovarian tissue was demonstrated in a xenografting model [18]. In another study, however, ovarian tissue from patients in complete remission did not appear to contain any viable malignant cells; although PCR results were positive, none of the grafted mice developed the disease [21].…”
Section: Introductionmentioning
confidence: 99%